DETERMINING COGS BASED ON CHANGES IN RAW MATERIAL PRICES IN THE RO HEMAT JAYA CRACKERS BUSINESS PURWAKARTA - Puspasari, Dewi; Saodah, Ai (Yayasan Pendidikan Belajar Berdikari, 2024)
This study analyzes the problem of determining the cost of goods sold (COGS) at Kerupuk RO Hemat Jaya Business due to fluctuations in raw material prices. The purpose of this study is to determine the impact of changes in raw material prices on COGS and to determine the appropriate method for calculating COGS. This study uses quantitative data such as raw material price data and production data, as well as qualitative data from interviews and direct observations. The results of the study indicate that fluctuations in raw material prices cause instability in COGS, making it difficult to determine the right selling price and impacting business profitability. The full costing method is recommended for calculating COGS because it takes into account all production costs, both fixed and variable. This study provides recommendations for better raw material management strategies and selling price determination to increase business profitability.